Roommate matching system - Nur Kamilah, Mohd Alias (Universiti Malaysia Sarawak, (UNIMAS), 2006)
MyRoommates is developing to overcome the roommate matching problem that most likely to occurs as soon as the new semester begins. This situation is faced by most senior students of University Malaysia Sarawak. Also the roommate matching system is expected to be helpful for the Desa Ilmu residence in searching for either roommates or rooms at the housing area. Therefore, the system domain covered Unimas campus area, which is specifically refer to the student hostels and Desa Ilmu housing area. The system provides two kind of member status; Student and Desa Ilmu residence. Also, there are two types of search; Roommates and Rooms. In order to use the system, user need to become a member by registering as a new member. Once registered, the member has to create a profile to generally describe about themselves. The system is implemented using Object-Oriented Development Lifecycle (OODLC) methodology. This methodology is divided into three macro phase which are Object-Oriented Analysis (OOA), Object-Oriented Design (OOD) and Object-Oriented Implementation. In the Object-Oriented Analysis phase, the requirements of the system need to identify such as user requirements in term of functional and non-functional requirement, targeted users, hardware requirements and software requirements. Later, based on these requirements a use case diagram model is illustrated to model the actor and use cases of the system. Through use case diagram model, designers can have a glance at the system functionality. Following the use case diagram model are class diagram or object model and activity diagram model. In Object-Oriented Design phase, the sequence diagrams are developing. These sequence diagrams shows the sequences taken in order to complete a single use case where each use case representing the function that provides by the system. Also the database is design using Entity Relationship diagram model. Finally, in the Object-Oriented Implementation phase, both component and deployment diagram are illustrated which show the relationship between software and hardware respectively. Next, the implementation of the system module is presented through screen snapshot. Once implemented, the system is tested to confirm that it met the requirement. Defect testing is conducted, by testing the system with incorrect input. The test will exhibit the response between the user and system. The last chapter is focus on the future works of the system. Suggestions have been included on how to enhance the system in future.